Perampasan Aset Tanpa Pemidanaan dalam Tindak Pidana Korupsi - Nurdiana Yuniar Kusumawardhani; Ariyanda Tri Firanti; Rafferty Cullen Mantaria (UNES Law Review, 2024)
Corruption can occur anywhere, not only in government bureaucracy or in the judicial environment known as judicial corruption, but also in companies, foundations, political parties, hospitals, and even in religious institutions. Non-Conviction Based (NCB) asset forfeiture or confiscation of assets resulting from criminal acts with a mechanism without punishment. This mechanism allows the confiscation of assets resulting from criminal acts in rem (against assets) not against the perpetrators of corruption. Land rights consist of primary rights and secondary rights, which are obtained through an agreement between the landowner and the prospective holder of secondary rights. Thus, the Non-Conviction Based Asset Forfeiture mechanism is an effective way to make the crime unprofitable because the perpetrators will think again about the consequences that will arise later. The concept of Non-Conviction Based Asset Forfeiture has become a legal necessity in Indonesia because the Non-Conviction Based Asset Forfeiture mechanism is an alternative to recover state assets lost due to criminal acts related to the country's economy by perpetrators of crimes to hide their assets. The implementation of a restorative justice concept also prioritizes the fulfillment of human rights in asset confiscation efforts, because the asset confiscation analyzed is a civil asset confiscation, so that the pursuit is not on the perpetrator but on the frozen assets.